Characteristics of Abs and Pla Material in 3D Printing for Car Backseat Headrest Hanger/Hook Model - Huvat, Rohana; bin Azizul, Muhamad Asri; bin Sulaiman, Syabillah (Journal of Automotive Powertrain and Transportation Technology, 2021)
Additive manufacturing (AM) is known as the technology which enable using a layer wise in fabrication of a complex part directly from CAD files without using any specific tooling. This manufacturing techniques offers many strategic advantages which include design freedom for the build of complex part geometries which cannot be made in other way, the ability to build functional part in a small size for the end user customization and its ability to do improvement for the expensive part in aerospace and other industries. The aim of this research is to study the effect of process parameter such as layer thickness, infill density and object orientation to the accuracy of printed part measurement with CAD model, surface roughness and mechanical strength of PLA and ABS material. Therefore, it is important to find the optimum value of dimensional accuracy, surface roughness and mechanical strength for both materials. To achieve the optimum value of dimensional accuracy, surface roughness and mechanical strength for both materials, Taguchi method L4 orthogonal array is used to conduct this experiment and Minitab 18 software will analyze the result and shows the best optimum value. The result from ANOVA analysis shows that object orientation gives highest contribution to the dimensional accuracy and surface roughness for both materials. Meanwhile, for mechanical strength layer thickness highly contributed to the ABS material and object orientation for the PLA material. A Car Backseat Headrest Hanger/Hook model is fabricated by the best optimal combination and level of process parameter of mechanical strength.